2020
DOI: 10.1371/journal.pone.0242001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal care coverage and correlates of HIV testing in sub-Saharan Africa: Insight from demographic and health surveys of 16 countries

Abstract: Background Prenatal screening of pregnant women for HIV is central to eliminating mother-to-child-transmission (MTCT) of HIV. While some countries in sub-Saharan Africa (SSA) have scaled up their prevention of MTCT programmes, ensuring a near-universal prenatal care HIV testing, and recording a significant reduction in new infection among children, several others have poor outcomes due to inadequate testing. We conducted a multi-country analysis of demographic and health surveys (DHS) to assess the coverage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
2
31
0
2
Order By: Relevance
“…In their study of ANC HIV testing in 18 SSA countries, they found that HIV testing is only mandatory in Rwanda and Uganda and there is evidence that "a large portion of women who received ANC are not tested for HIV in some SSA countries." 43 We also found that good testing and ARV adherence behaviors appear to flow down to others within the same household. Heads of households who are HIV positive increase the likelihood that others in the household get tested (likelihood of awareness is much higher than for those living in a household without an HIV-positive household Household factors associated with managing the HIV positive population and meeting the UNAIDS goals Journal of Global Health Reports head) and VLS24 is also much higher.…”
Section: Summary Of Vls Barriersmentioning
confidence: 55%
See 2 more Smart Citations
“…In their study of ANC HIV testing in 18 SSA countries, they found that HIV testing is only mandatory in Rwanda and Uganda and there is evidence that "a large portion of women who received ANC are not tested for HIV in some SSA countries." 43 We also found that good testing and ARV adherence behaviors appear to flow down to others within the same household. Heads of households who are HIV positive increase the likelihood that others in the household get tested (likelihood of awareness is much higher than for those living in a household without an HIV-positive household Household factors associated with managing the HIV positive population and meeting the UNAIDS goals Journal of Global Health Reports head) and VLS24 is also much higher.…”
Section: Summary Of Vls Barriersmentioning
confidence: 55%
“…These programs generally include mandatory HIV testing coupled with other informational services for pregnant women. 43 This widespread program activity may be 'creating' the apparent gender gap for awareness and/or VLS by including testing, counseling, and even preemptive ARV treatment as part of antenatal and institutional birthing services for pregnant women. A study of the community impact of a new PMTCT program in a high prevalence area in South Africa shows that widespread PMTCT programs may explain the gender gap we see in HIV awareness and viral suppression.…”
Section: Analysis Of the Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a strong association between pregnancy and self-reported HIV testing. This could mainly be attributable to the wide access to HIV testing among pregnant women attending antenatal clinic (ANC) visits [ 16 ]. Several studies have also found this association [ 13 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited prenatal HIV testing in sub-Saharan Africa (6.1%-98.1%) [1], the integration of HIV testing and counselling into antenatal care has averted over two million paediatric infections in the past two decades [2]. However, undetected acute HIV infections during pregnancy and postpartum pose significant challenges to PMTCT efforts [3,4].…”
Section: Introductionmentioning
confidence: 99%